Infecção experimental de coelhos e camundongos com o vírus do ectima contagioso - Cargnelutti, Juliana Felipetto (2010)
Contagious ecthyma (orf) is a cutaneous disease that affects sheep and goats, and may be occasionally transmitted to humans. The disease is caused by orf virus (ORFV). ORFV infection produces croustous and proliferative lesions, usually on the nostrils and labial commissures of lambs, and also in the udder, teat skin and coronary bands of adults animals. The pathogenesis of ORFV infection is poorly understood and a search for an adequate animal model is required, yet the disease has been already reproduced in sheep, goats and rabbits. This dissertation relates the clinical, virological and pathological aspects of ORFV infection in rabbits and mice experimental inoculated. Ten rabbits, ten mice and two lambs were inoculated intradermally after skin scarification with an hypodermic needle. A viral suspension of ORFV IA-82 strain (108.5TCID50/mL) was inoculated in the internal face of the ear, back skin and labial commissure of rabbits; internal face of the ear of mice. Lambs were inoculated in the labial commissures and in the internal face of hind limbs. All animals were monitored clinically, virologically, and pathologically for 21 days. All rabbits developed clinical signs in the inoculation sites, begining with mild hyperemia that evolved to macules, papules, vesicle, pustules and scabs. Lesions appeared at days 3 and 4 post-inoculation (pi) and lasted to 3 to 10 days. Viral shedding was detected from days 2 to 14pi. Histological examination of lesions revealed focal proliferative dermatitis with ballooning degeneration and eosinophilic intracytoplasmic inclusions in keratinocytes, histological hallmarks of contagious ecthyma in sheep. A similar, albeit much milder clinical course was observed in 5 out of 10 inoculated mice. All lambs presented characteristic contagious ecthyma clinical and histopathologycal lesions from days 3 to 18pi, and the virus was recovered from lesions between days 2 and 19pi. At day 28pi, seroneutralization test (SN) was unable to detect neutralizing antibodies in all inoculated animals. These findings show that ORFV replicates and produce local lesions in rabbits and mice. However, rabbits are more susceptible to infection and disease, and may be used as an animal model to study some aspects of ORFV pathogenesis.